An Inquiry into the Relationship between Liquidity Management and Profitability of MSMEs as Tools of Poverty Alleviation - Sazir Nsubuga Mayanja (International Journal of Small and Medium Enterprises and Business Sustainability, 2022)
The study was intended to establish whether there is a relationship between liquidity management and profitability of micro, small and medium-scale enterprises (MSMEs), which are tools of poverty alleviation, among other functions in an economy. A cross-sectional descriptive design involving both qualitative and quantitative approaches was adopted. A sample of 371 respondents was systematically sampled from four districts of Wakiso, Mukono, Kampala, and Jinja in Uganda. Findings revealed that liquidity management practices of MSMEs were ineffective, negatively impacting their profitability. Matching source and maturity terms of funds with activities and professionalized cash planning and investment are among our recommendations.